Pengembangan Objek Wisata Pemandian Air Panas Sungai Pinang Kabupaten Kuantan Singingi - Alan Dafrina Agusta; Zulkarnaini Zulkarnaini (Peneliti.net, 2022)
The Hot Springs tourist attraction located in Sungai Pinang Village, Kuantan Singingi Regency has potential that can be developed and utilized to attract tourists. However, its management is still hampered by the availability of funds that can be used. So in this case a development of this tourist attraction. This study aims to determine the development strategy and the inhibiting factors in the development of hot spring tourism object of Sungai Pinang. This study uses qualitative research methods with data collection techniques by observation, interviews and documentation. This research has the result that the development that has been carried out has been going well, as evidenced by the fact that initially only a well became a hot water bath that could be enjoyed. The obstacles in its development are the limited budget allocated for the development of this tourist attraction and the initial plan was 2 adult pools and 1 children`s pool to become 1 adult pool and 1 kids pool.